Temperature-controlled hydrogenation of anthracene over nickel nanoparticles supported on attapulgite powder. (1st July 2018) - Liu, Zhong-Qiu; Wei, Xian-Yong; Liu, Fang-Jing; Wang, Bao-Jun; Zong, Zhi-Min
Graphical abstract: Abstract: Catalyst Ni/attapulgite powder (AP) was facilely prepared by thermally decomposing nickel tetracarbonyl onto AP. Anthracene was used as a condensed arenes (CAs)-related model compound to evaluate the catalytic activity and selectivity of Ni/AP for hydrogenating CAs. The results show that anthracene can be completely converted to perhydroanthracenes (PHAs) at 175 °C and selectively converted to 9, 10-dihydroanthracene (DHA, ca. 86.4%) at 300 °C by catalytic hydrogenation over Ni/AP. Ni/AP effectively promotes the formation and transfer (F & T) of biatomic active hydrogen (H⋯H) at 175 °C, resulting in the complete hydrogenation of anthracene to PHAs. The mechanism for the F & T of H⋯H is consistent with the observation from the higher selectivities of cis- PHAs than that of trans- PHAs. At 300 °C, the catalytically produced H⋯H over Ni/AP tends to be homolytically spitted to hydrogen radical (H ), inducing the partial hydrogenation of anthracene to DHA. Quantum chemical calculations based on density functional theory further confirmed the temperature-controlled hydrogenation of anthracene over Ni/AP. This finding is a conclusive proof that the active hydrogen species is crucially important for affecting the product selectivities from the catalytic hydrogenation of anthracene over Ni/AP. Our research also offers a novel strategy for highly selective conversion of CAs to polycyclic alkanes or hydroarenes.